Analisis Citraan dalam Buku Kumpulan Puisi Melodi Hujan Tiris Puisi-Puisi Cinta Karya Marhalim Zaini - Muhammad Arief; Sri Rahayu (UIR Press, 2023)
Language is the main medium for conveying ideas, ideas, feelings, souls and experiences of poets in a literary work. This book, a collection of poems by Marhalim Zaini, contains imagery and tells about the world of poet love. The problem studied in this study is how the imagery is contained in the poetry collection book Melody Rain Tiris Poems of Love by Marhalim Zaini. The aim of this research is to know, analyze and interpret imagery data in poetry. This study uses a qualitative approach to the type of library research. The method used is descriptive method and uses data collection techniques with hermeneutic techniques. Data analysis technique used content analysis technique and data validation technique used triangulation technique. The book of poetry collection Melody of Rain Tiris Poems of Love by Marhalim Zaini brings to the imagination that stimulates the five human senses and describes the story of love, turmoil and the process of the poet's romance. The results of research on imagery contained in the poetry collection book Melody Rain Tiris Poems of Love by Marhalim Zaini found that visual imagery is more dominant. The six types of imagery in the poem can describe and feel something in the poem that allows the reader to describe from the poet's perspective, thoughts, feelings, depiction of the poet's condition and creates an atmosphere and expression.